Side-chain engineering on conjugated porous polymer photocatalyst with adenine groups enables high-performance hydrogen evolution from water. (1st February 2022) - Li, Renlong; Zhang, Chong; Cui, Cheng-Xing; Hou, Yuxia; Niu, Hongying; Tan, Ching-Hong; Yang, Xiye; Huang, Fei; Jiang, Jia-Xing; Zhang, Yuping
Abstract: Conjugated polymers have been investigated widely as encouraging photocatalysts for hydrogen production. However, it is still arduous for polymer photocatalysts to achieve high photocatalytic activity under visible light. Herein, we demonstrate an efficient design to enhance the hydrogen evolution rate (HER) of conjugated polymers through the modification of surface chemistry by introducing the hydrophilic adenine group onto the side chain. The adenine group with plentiful nitrogen atoms can form multiple hydrogen bonds with water molecules, which improve the interactions between the resulting polymer surface and water molecules, leading to improved hydrophilicity and dispersity of the polymer photocatalyst in photocatalytic reaction solution. Density functional theory calculation indicated that the introduction of adenine groups also leads to the enhanced separation of the electrostatic potential on the surface of polymer photocatalyst, which is favorable for the photocatalytic hydrogen evolution reaction. Therefore, a high HER of 36.43 mmol h −1  g −1 was achieved by the adenine-functionalized polymer PF6A-SF without using Pt cocatalyst, which is almost 42 times higher than that of the alkyl-functionalized polymer PF6-SF (0.87 mmol h −1  g −1 ), demonstrating that rational design of side-chain engineering is an effective design for organic photocatalysts with high photocatalytic activity. Graphical abstract: We designed and constructed an adenine-functionalized conjugated polymer PF6A-SF as an efficient photocatalyst for hydrogen evolution from water. Without using Pt cocatalyst, a 42-fold improvement in hydrogen evolution rate has been achieved than that of alkyl-functionalized conjugated polymer PF6-SF, which represents the state-of-the-art organic polymer photocatalysts. Image 1 Highlights: An adenine-functionalized conjugated porous polymer was developed for highly efficient photocatalytic hydrogen evolution. The intimate contact between adenine groups and water molecules enables more efficient charge transfer and separation. The bare adenine-functionalized conjugated polymer achieved a high HER of 36.43 mmol g −1  h −1 .